Color quality, behavioral response, and blood glucose levels of guppies Poecilia reticulata (Peters, 1859) with the addition of Indian almond leaves (Terminalia catappa) in fish containers - Izhar Amirul Haq; Kukuh Nirmala; Yuni Puji Hastuti; Eddy Supriyono (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2022)
Guppies are ornamental fish that have economic value and can be cultivated. One of the problems in guppies cultivation is the poor quality of body color. The solution to this problem is to improve the environmental quality in guppy aquaculture. This study evaluates changes in color quality, behavioral response, and blood glucose levels of guppies using water immersion of Indian almond leaves on rearing media. Study was carried out using a completely randomized design consisting of five treatments. The rearing media was filled water with a total volume of 10 L from each treatment with different concentrations, namely, Control treatment (100% freshwater), A (75% freshwater + 25% Indian almond leaf water), B (50% freshwater + 50% Indian almond leaf), C (25% freshwater + 75% Indian almond leaf) and D (100% Indian almond leaf). Each treatment observed several test parameters such as color quality percentage, survival rate, chromatophores cells number, behavior, glucose levels, and the water physical-chemical parameters. Guppies' behavioral responses, in general, experienced an increasing change in each treatment for seven days. The highest color quality percentage by treatment D was 73.93±2.29%, and the highest glucose level was by the control treatment, which was 24.11±0.41 mg dL-1. The results of variance analysis showed that the water immersion of Indian almond leaves was significantly different on color quality, behavioral response, and blood glucose levels through Duncan's test (p<0.05). Abstrak Ikan guppy termasuk ikan hias yang memiliki nilai ekonomis dan dapat dibudidayakan. Salah satu masalah dalam budidaya ikan guppy yaitu kualitas warna tubuhnya yang tidak bagus. Upaya yang dapat dilakukan yaitu memperbaiki lingkungan budidaya ikan guppy. Studi ini bertujuan untuk mengevaluasi perubahan kualitas warna, respons tingkah laku, dan kadar glukosa ikan guppy menggunakan rendaman air daun ketapang pada media pemeliharaan. Evaluasi ini dilakukan dengan menggunakan rancangan acak lengkap yang terdiri atas lima perlakuan. Media pemeliharaan diisi air dengan total volume 10 L dari setiap perlakuan dengan konsentrasi yang berbeda yaitu, perlakuan Kontrol (100% air tawar), A (75% air tawar + 25% air daun ketapang), B (50% air tawar + 50% air daun ketapang), C (25% air tawar + 75% air daun ketapang) dan D (100% air daun ketapang). Setiap perlakuan diamati beberapa parameter uji seperti persentase kualitas warna, tingkat sintasan, jumlah sel kromatofora, tingkah laku, kadar glukosa, dan parameter fisik kimiawi perairan. Respons tingkah laku ikan guppy secara umum mengalami perubahan yang meningkat dalam setiap perlakuan selama tujuh hari. Persentase kualitas warna tertinggi pada perlakuan D yaitu sebesar 73,93±2,29% dan nilai kadar glukosa tertinggi pada perlakuan Kontrol yaitu 24,11±0,41 mg dL-1. Hasil analisis sidik ragam menunjukkan bahwa rendaman air daun ketapang berbeda nyata terhadap kualitas warna, respons tingkah laku dan kadar glukosa darah melalui uji Duncan (p0,05).